The association between maternal anthropometry and blood pressure in pregnancy : results from the Croatian islands’ birth cohort study (CRIBS) - Šarac, Jelena (Array, 2019)
Elevated blood pressure (BP) in pregnancy, especially gestational hypertension and preeclampsia, can lead to serious pregnancy complications and adverse birth outcomes. A large body of literature already reported the effect of baseline body mass index (BMI) on changes in blood pressure during pregnancy. The aim of this study was therefore to define trajectory of systolic (SBP) and diastolic (DBP) blood pressure in 308 pregnant participants from the CRIBS study (146 from the mainland and 162 from the islands of Brač and Hvar) and to analyze the association of blood pressure with maternal BMI prior to pregnancy and maternal anthropometry during pregnancy. Pregnant women included in the CRIBS study had no history of chronic diseases. The BP of CRIBS participants was measured at least once in each trimester, and maternal pre-pregnancy weight was self-reported. All analyses were performed using SPSS 10.0. Results showed that pre-pregnancy BMI was the strongest predictor of pregnancy blood pressure. This association was evident for pre-pregnancy BMI independently (p<0.001), and it also persisted after adjusting for maternal age, education, income, parity, smoking and physical activity (p<0.05). The association between maternal anthropometry during pregnancy and blood pressure was not as strong and was therefore less informative. The study reinforces the role of BMI on SBP and DBP and highlights its importance during prenatal care monitoring. Significant association also emerged between blood pressure in pregnancy and place of residence (mainland vs. island). Women on Dalmatian islands have lower educational level, higher pre-pregnancy BMI and different levels of blood pressure than women from the mainland (namely, higher SBP and lower DBP). Such comparisons between mainland and island populations are valuable, because they can, in the long term, lead to better maternal health care on the islands.